America, goddam: violence, black women, and the struggle for justice - Lindsey, Treva B. (University of California Press, 2022)
A powerful account of violence against Black women and girls in the United States and their fight for liberation. America, Goddam explores the combined force of anti-Blackness, misogyny, patriarchy, and capitalism in the lives of Black women and girls in the United States today. Through personal accounts and hard-hitting analysis, Black feminist historian Treva B. Lindsey starkly assesses the forms and legacies of violence against Black women and girls, as well as their demands for justice for themselves and their communities. America, Goddam powerfully demonstrates that the struggle for justice begins with reckoning with the pervasiveness of violence against Black women and girls in the United States. Combining history, theory, and memoir, America, Goddam renders visible the gender dynamics of anti-Black violence. Black women and girls occupy a unique status of vulnerability to harm and death, while the circumstances and traumas of this violence go underreported and understudied. Lindsey also shows that the sanctity of life and liberty for Black men has been a galvanizing rallying cry within Black freedom movements. But Black women—who have been both victims of anti-Black violence as well as frontline participants in it, and quite often architects of these freedom movements—are rarely the focus. Black women have led movements demanding justice for Breonna Taylor, Sandra Bland, Toyin Salau, Riah Milton, Aiyana Stanley-Jones, and countless other Black women and girls whose lives have been curtailed by numerous forms of violence. Across generations and centuries, their refusal to remain silent about violence against them led many to envisioning and building toward Black liberation through organizing and radical politics. Echoing the energy of Nina Simone's searing protest song that inspired the title, America, Goddam is a call to action in our collective journey toward just futures